Engaging with materialism and material reality: Critical disability studies and economic recession - Flynn, Susan (My University, 2017)
Critical disability studies has been accused of preoccupation with cultural, lingual and discursive matters, and in doing so failing to adequately engage with the often-harsh material reality of disability. This has contributed to a circumstance in which disability studies has produced a lack of material focused directly upon economic processes. Concurrently, disabled people have encountered a momentous economic recession that has threatened their basic economic and human rights. This article seeks to address what is evidently a gap in the burgeoning critical disability and disability studies literature. That is, a gap largely uninhabited by attempts to apply a critical disability studies perspective to macro-economic processes. The article focuses predominantly on two facets of critical disability studies as identified by Goodley: the self and other, and intersectionality. The article concludes that critical disability studies has much to offer through the production of new understandings of economic processes.
PUBLISHED
Keywords: Critical disability studies; Economic recession; Materialism; Neo-liberalism; Inclusive Society; Families & Social Change; Social Work; Social exclusion